Pak̲h̲tūn samāj : maz̲habī, samājī, s̲aqāfatī, iqtiṣādī aur siyāsī pahlū - Yūsufzaʼī, Iʻjāz Aḥmad (Rāvalpinḍī : Rumail Hāʼūs āf Pablīkeshanz, 2015)
Study of the Pushtuns customs and traditions.
"Iz̤āfahʹshudah aiḍīshan".
Includes bibliographical references (pages 143-144).
In Urdu.
Keywords: Pushtuns -- Social life and customs; Pushtuns; Pushtuns; Pushtuns -- Social life and customs